Upaya perlindungan terhadap COVID-19 pada ingroup dan outgroup - Faturochman Faturochman; Wenty Marina Minza (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2022)
Various efforts have been carried out to protect oneself and one’s group from the threat of COVID-19. In reality, it is possible that there are different mechanisms to protect the group. Ingroup favoritism is likely to occur, even in times of pandemic. This study aims to explore the differences in protective behaviors (toward ingroups vs. outgroups) and investigate the differentiating factors leading to protective behaviors. Through an online survey, a total of 593 respondents filled out a questionnaire that measures ingroup and outgroup protection, self-protection, and collective coping. The results of the data analysis show the tendency for ingroup favoritism in efforts to protect the group. Further analysis shows that efforts to protect the ingroup are influenced by collective coping and self-protection, while efforts to protect the outgroup are only influenced by collective coping. These findings strengthen the perspective that collectivity is the basis for protection from COVID-19 in general, while individual factors lead to greater ingroup protection.